Social Media Marketing Strategy Analysis of @Citraraya Instagram in Promoting Properties - Shabrina, Almira (JIKE : Jurnal Ilmu Komunikasi Efek, 2023)
The 0% DP (down payment) policy for housing purchase loans (KPR) issued by Bank Indonesia was able to restore the property industry in Indonesia, including Tangerang area, which experienced the highest price change index of 6.8%. One of the property development areas in Tangerang Region is Citra Raya which located in Cikupa, Tangerang Regency. Citra Raya uses Instagram social media to carry out property promotion activities in accordance with the target market for property sales and has managed to get the highest number of followers when compared to competitor Instagram accounts in the Tangerang Region. The purpose of this study is to analyze the Instagram social media marketing strategy carried out by Citra Raya in promoting property. The research method used descriptive qualitative with data collection techniques through in-depth interviews, documentation, observation, and literature study. The results of this study were analyze using the theory of social media marketing success according to Gurnelius (2019) in the form of Content sharing, Content Creation, Connecting, and Community Building. The conclusion of this research is that the difference in product prices determines the content approach created, the use of Instagram Ads is the main focus of Citra Raya's social media marketing activities which are able to generate sales and expand the online audience. However, the lack of human resources at Citra Raya makes the communication process with the audience and the use of features on Instagram not optimal, as well as the lack of diversity in types of content.